2018
DOI: 10.1127/anthranz/2018/0782
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smoking and BMI differences between smokers and non-smokers among children and adolescents aged 7–18 years in south-east Poland

Abstract: : The aim of the study was to determine the prevalence of smoking among children and adolescents aged 7-18 years, and also to determine the relationship between this addiction and the Body Mass Index (BMI). : Basic anthropometric measurements were performed, and information concerning cigarette smoking and basic SES was gathered using the questionnaire method.: More than 5% of boys admit to smoking at the age of 10-11 years, and as many as 22% 18-year-olds admit to doing so. With regard to girls, the situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In advanced cases, on the other hand, malnourishment and low BMI pose a serious threat to overall health and can have negative effects on tumor therapy (39,40). Tobacco smoking can be associated with low socioeconomic status and higher BMI but also coincided with lower BMI in other studies (41)(42)(43). A poor diet, low in fruit and vegetables, has been correlated with oral cancer, and it has been shown that a Mediterranean diet favorably affects the risk of upper aerodigestive tract cancer (44,45).…”
Section: Discussionmentioning
confidence: 92%
“…In advanced cases, on the other hand, malnourishment and low BMI pose a serious threat to overall health and can have negative effects on tumor therapy (39,40). Tobacco smoking can be associated with low socioeconomic status and higher BMI but also coincided with lower BMI in other studies (41)(42)(43). A poor diet, low in fruit and vegetables, has been correlated with oral cancer, and it has been shown that a Mediterranean diet favorably affects the risk of upper aerodigestive tract cancer (44,45).…”
Section: Discussionmentioning
confidence: 92%